2002
DOI: 10.1159/000065001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Methyl Parathion: A Comparison following Single Intravenous, Oral or Dermal Administration

Abstract: Assessment of the risks posed by the residential use of methyl parathion requires an understanding of its pharmacokinetics after different routes of exposure. Thus, studies were performed using adult female rats to define the pharmacokinetic parameters for methyl parathion after intravenous injection and to apply the described model to an examination of its pharmacokinetics after single oral or dermal exposure. The pharmacokinetics of methyl parathion after intravenous administration (1.5 mg/kg) were best desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Toxicokinetic studies in rats exposed to a single dose (10 mg/kg) of PT showed that it accumulated in fat tissue (67 lg/mL) and also in some other organs, including the liver (706 ng/mL) [Abu-Qare et al, 2000]. Another study showed that PT was detectable in rat liver after 1 hr of exposure [Kramer et al, 2002]. These studies showed that the concentration of OPs in liver is much higher than in plasma.…”
Section: Discussionmentioning
confidence: 97%
“…Toxicokinetic studies in rats exposed to a single dose (10 mg/kg) of PT showed that it accumulated in fat tissue (67 lg/mL) and also in some other organs, including the liver (706 ng/mL) [Abu-Qare et al, 2000]. Another study showed that PT was detectable in rat liver after 1 hr of exposure [Kramer et al, 2002]. These studies showed that the concentration of OPs in liver is much higher than in plasma.…”
Section: Discussionmentioning
confidence: 97%
“…injection and determined using a standard method with linear and log-linear least squares regression analysis to determine the various parameters (Kramer et al 2002;Watanabe et al 1986). The area under the concentration versus time curves from time zero to infinity (AUC 0- ) was calculated by the trapezoidal rule, with extrapolation to infinity by dividing the last measurable blood concentration by the elimination rate constant (β).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The studies on pharmacokinetics of MP through different routes of exposure suggested dermal exposure, which is the mode of exposure most likely to occur in domestic setting, increases the potential for long-term, adverse health effects [11]. In our previous study, we mimicked dermal exposure condition in a rat model.…”
Section: Introductionmentioning
confidence: 99%